(untitled) (Annual Transactions of the Nordic Rheology Society, 2025)
Bitumen and polymer blends represent important compounds for the production of waterproofing membranes for the roofing industry. The addition of a polymer is fundamental to improving performance and mechanical characteristics. On the other hand, compatibility between asphalt and polymers is a crucial factor which deeply affect the thermo-mechanical and rheological properties of bituminous compounds. As a matter of fact, the low compatibility between polymer and bitumen is the root of many problems in the formulation of bituminous blends. A careful selection of the raw materials needed for the optimization of the final characteristics for the formulation of the bitumen-polymer compounds, used in the production of waterproofing membranes. Polyolefins and elastomers are commonly used in this kind of product, thanks to their compatibility with bitumen. The following study investigates the role of quantity and type of polymer to produce bituminous waterproofing membranes, by comparing the performance of different bitumen and polymer combinations (radial and linear SBS) through rheological tests. The bituminous compounds were tested with a strain-controlled rheometer by using a “temperature sweep” protocol, an oscillatory test in which both components of the moduli (G’, elastic, and G’’, viscous) were evaluated by cooling the sample at a fixed frequency within the viscoelastic region. This kind of analysis gives an interesting insight into the behaviour of the bituminous compounds in a wide range of temperatures.